2016
DOI: 10.5334/pb.301
|View full text |Cite
|
Sign up to set email alerts
|

A Validation of the French Version of the Attitudes to Aging Questionnaire (AAQ): Factor Structure, Reliability and Validity

Abstract: Introduction: The Attitudes to Aging Questionnaire (AAQ) was developed to measure attitudes toward the aging process as a personal experience from the perspective of older people. The present study aimed to validate the French version of the AAQ.Participants and methods: This study examined factor structure, acceptability, reliability and validity of the AAQ’s French version in 238 Belgian adults aged 60 years or older. In addition, participants provided information on demographics, self-perception of their me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…In this study, similar to previous findings, education was associated with positivity towards ageing among rural and urban older persons [ 5 , 10 , 12 , 37 , 38 ]. Also, previous research has shown that the combination of living in urban settings and a high level of education indicate higher social status [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, similar to previous findings, education was associated with positivity towards ageing among rural and urban older persons [ 5 , 10 , 12 , 37 , 38 ]. Also, previous research has shown that the combination of living in urban settings and a high level of education indicate higher social status [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…Other translated versions of the AAQ in various countries also showed three-factor structures similar to that of the original AAQ. 7 , 8 , 13 - 15 ) However, the final AAQ-M included only 19 items. Five items were removed: three for poor factor loading and two for incorrect loading and contextually inappropriate factors.…”
Section: Discussionmentioning
confidence: 99%
“… 12 ) The questionnaire has been translated into various languages and validated in many countries, including Canada, Spain, Brazil, Iran, Norway, and Belgium. 8 , 13 - 15 ) To our knowledge, no validated tool was available in Malay to measure the attitude toward aging among older adults in Malaysia. Research on the attitudes of Malaysian older adults toward aging is also limited.…”
Section: Introductionmentioning
confidence: 99%
“…We estimated reliability (internal consistency and test-retest reliability) and construct validity (discriminant and structural). To provide external measures, we compared the UCLA-GAS-F to the Aging Stereotypes and Exercise Scale (ASES) initially developed in French [ 28 ] and seven selected items, which can be addressed by a large public, of the French version of the Attitudes to Aging Questionnaire (AAQ) [ 29 ]. The local Ethics Committee approved the study (Req-2018-00467) according to the Swiss law [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Higher total scores indicate larger positive attitudes towards one’s own aging process. The scale was assessed for validity and reliability in French and demonstrated acceptable psychometric qualities [ 29 ]. We selected the first seven items of the scale as they are more general and can be addressed by a large public.…”
Section: Methodsmentioning
confidence: 99%